A Pilot Study of Estradiol Followed by Exemestane for Reversing Endocrine Resistance in Postmenopausal Women With Hormone Receptor‐Positive Metastatic Breast Cancer. (26th September 2014) - Chalasani, Pavani; Stopeck, Alison; Clarke, Kathryn; Livingston, Robert
Abstract : Background: Endocrine resistance is a frequent complication, and strategies to reverse it are a high research priority for metastatic breast cancer (MBC) that is hormone receptor positive. Preclinical data suggest re‐exposure to estrogen induces tumor regression in tamoxifen‐resistant tumors. We conducted a pilot study to determine whether short‐term estradiol exposure would reverse endocrine resistance and resensitize tumors Methods: Postmenopausal women with estrogen receptor‐positive MBC whose disease had progressed after receiving at least one prior endocrine therapy were eligible for the study. Patients were initially treated with 6 mg/day estradiol, and those who had not progressed after 3 months were then switched to exemestane. Results: Thirteen patients were evaluable for toxicity and response. No grade 3 or 4 toxicities were observed. Of the 13 patients who initiated estradiol therapy, 6 patients (46%) had not experienced disease progression at month 3 and were switched to exemestane. On exemestane, disease progression was documented in five patients, with one having stable disease as best response. Median progression‐free survival for all patients was 4.8 months (range: 0.6–9.5 months). Conclusion: Treatment with an estrogen prior to resuming antiestrogen treatments was not effective at reversing hormone resistance; however, low‐dose estradiol treatment had measurable clinical activity with minimal toxicity and should be considered as a therapeutic option for hormone‐refractory MBC. Abstract : 摘要 背景 . 内分泌治疗耐药是激素受体阳性的转移性乳腺癌（MBC）常见的并发症，逆转内分泌治疗耐药的策略已成为研究的重中之重。临床前数据提示，再次暴露于雌激素可诱导他莫昔芬耐药肿瘤再次缩小。我们开展了一项初步研究，旨在明确短期雌二醇暴露能否逆转内分泌耐药以及使肿瘤恢复敏感性。 方法 . 入组标准为雌激素受体阳性的绝经后 MBC 患者，且既往接受过至少 1 次内分泌治疗后疾病进展。入组后，初期给予 6 mg/d 雌二醇治疗，3 个月后未发生疾病进展者转换为依西美坦治疗。 结果 . 13 例患者毒性反应和缓解率可评估。未观察到 3 或 4 级毒性反应。接受雌二醇起始治疗的 13 例患者中，6 例（46%）在 3 个月时未发生疾病进展，进而转换为依西美坦治疗。接受依西美坦治疗的患者中有 5 例发生疾病进展，其中 1 例最佳缓解状态为疾病稳定。全部患者的中位无进展生存为 4.8 个月（范围：0.6∼9.5 个月）。 结论 . 在重新给予抗雌激素治疗之前，使用雌激素并不能有效逆转激素耐药；然而，低剂量雌二醇治疗具有一定的临床活性，毒性反应微乎其微，应考虑作为激素难治性 MBC 的治疗选择之一。 The Oncologist 2014;19: 1127‐1128